Bifidobacterium infantis Maintains Genome Stability in Ulcerative Colitis via Regulating Anaphase-Promoting Complex Subunit 7 - Han, Taotao; Hu, Xiaomin; Li, Kemin; Zhang, Di; Zhang, Yan; Li, Jingnan (Frontiers in Microbiology, 2021)
Probiotics represents a promising intestinal microbiota-targeted therapeutic method for the treatment of ulcerative colitis (UC). Several lines of evidence implicate that Bifidobacterium infantis (B. infantis) severes as a probiotic strain with proven efficacy in maintaining the remission of UC. However, the exact mechanisms underlying the beneficial effects of B.infantis on UC progression have yet to be elucidated. Herein, we provide evidence that B.infantis acts as a key predisposing factor for the maintenance of host genome instability. First, we showed that the fecal microbiota transplantation (FMT) of UC-derived feces contributes to DNA damage in dextran sodium sulfate (DSS)-induced mice likely due to mucosa-associated microbiota alterations, as reflected by the rapid appearance of DNA double strand breaks (DSBs), a typical marker of genome instability. Genomic DNA damage analysis of colon tissues derived from healthy controls, patients with UC or dysplasia, and colitis associated cancer (CAC) patients, revealed an enhanced level of DSBs with aggravation in the degree of the intestinal mucosal lesions. To evaluate whether B.infantis modulates the host genome stability, we employed the DSS-induced colitis model and a TNFα-induced intestinal epithelial cell model. Following the administration of C57BL/6 mice with B.infantis via oral gavage, we found that the development of DSS-induced colitis in mice was significantly alleviated, in contrast to the colitis model group. Notably, B.infantis administration decreased DSB levels in both DSS-induced colitis and TNF-treated colonial cell model. Accordingly, our bioinformatic and functional studies demonstrated that B.infantis altered signal pathways involved in ubiquitin-mediated proteolysis, transcriptional misregulation in cancer, and the bacterial invasion of epithelial cells. Mechanistically, B.infantis upregulated Anaphase Promoting Complex Subunit 7 (APC7), which was significantly suppressed in colitis condition, to activate the DNA repair pathway and alter the genome stability, while downregulation of APC7 abolished the efficiency of B.infantis treatment to induce a decrease in the level of DSBs in TNFα-induced colonial cells. Collectively, our results support that B.infantis orchestrates a molecular network involving in APC7 and genome stability, to control UC development at the clinical, biological, and mechanistic levels. Supplying B.infantis and targeting its associated pathway will yield valuable insight into the clinical management of UC patients.